Analisis Hukum Terhadap Pengadaan Barang/Jasa Pemerintah Melalui Pembelian Secara Elektronik (E-Purchasing) Di Provinsi Gorontalo - Richie Z. Abdullah; Hijrah Lahaling; Rusmulyadi Rusmulyadi (Hakim, 2024)
E-purchasing in Gorontalo Province is not yet optimal, hindered by implementation obstacles and the potential for fraud. The lack of studies on the effectiveness of procurement of goods/services through e-purchasing is a concern. Juridical-normative research with a comparative and conceptual approach reveals that e-purchasing in the province is not fully effective. Implications include the potential for price manipulation, bribery, fictitious transactions, administrative malpractice, and inefficiency. The study highlights issues such as the potential for Price Setting by Procurement Service Unit and Providers, Bribery and Gratification Potential, Fictitious Transactions, Administrative Malpractice/Non-negotiation, Failure to Check Product Specifications, High Prices, Waste, and Inefficiency in the procurement of Goods/Services through e-purchasing in Gorontalo Province.